Disentangling the geographical logic of Airbnb in Switzerland - Doménech, Antoni; Larpin, Blaise; Schegg, Roland; Scaglione, Miriam (ERDKUNDE, 2019)
The unprecedented worldwide growth of Airbnb over the last decade deserves to be analysed from a geographical perspective so as to understand the underlying logic behind the spatial distribution of the accommodation offered on the platform. Multiple territorial and economic variables may influence this distribution. In this context, the article aims to analyse the spatial distribution of Airbnb in Switzerland and identify its determinants. Geographical Information Systems are used to analyse the geographical distribution of Airbnb listings, and Negative Binomial Models are applied to identify its determining factors. Results are particularly interesting as they highlight that Airbnb listings are mainly clustered geographically in specific areas of the country. The success of Airbnb as an accommodation supply platform has led to a concentration of Airbnb listings in areas of Switzerland where hotel supply is significant, but also in areas where there is a high presence of second homes and the potential for generating profit from the housing market is greater.